Calcium Signalling and Liver Regeneration - Isabelle Garcin; Thierry Tordjmann (International Journal of Hepatology)
After partial hepatectomy (PH) the initial mass of the organ is restored through a complex network of cellular interactions that orchestrate both proliferative and hepatoprotective signalling cascades. Among agonists involved in this network many of them drive Ca2+ movements. During liver regeneration in the rat, hepatocyte cytosolic Ca2+ signalling has been shown on the one hand to be deeply remodelled and on the other hand to enhance progression of hepatocytes through the cell cycle. Mechanisms through which cytosolic Ca2+ signals impact on hepatocyte cell cycle early after PH are not completely understood, but at least they include regulation of immediate early gene transcription and ERK and CREB phosphorylation. In addition to cytosolic Ca2+, there is also evidence that mitochondrial Ca2+ and also nuclear Ca2+ may be critical for the regulation of liver regeneration. Finally, Ca2+ movements in hepatocytes, and possibly in other liver cells, not only impact hepatocyte progression in the cell cycle but more generally may regulate cellular homeostasis after PH.